TO BE BRAVE: HEROISM AND BRAVERY IN NEIL GAIMAN’S CORALINE - DG, Sharanya (UC Journal: ELT, Linguistics and Literature Journal, 2024)
The paper explores the themes of Heroism and Bravery, which are abundant in Fantasy literature. With reference to the existing literature, these concepts are defined and differentiated, and their relevance in Fantasy literature is delineated. A close reading of Neil Gaiman’s Fantasy novel, Coraline (2002), is used to exemplify the use of these themes. I argue that heroism is a socially and historically constructed trope that defines the journey of the protagonist (typically, of a male “hero”), whereas bravery lies in individual acts of courage and determination in the face of danger. This line of argument is undertaken by conducting a formal and textual analysis of Coraline, providing ample references to the heroism and bravery of its protagonist, to highlight further how the novel helps its young readers deal with the realities of the world they live in.